Kinetic parameters obtained for thermal decomposition of acrylic resins present in commercial paint emulsions - Crespi, Marisa Spirandeli [UNESP]; Hikosaka, Marcia Yumi; do Amaral, Graziela Camas Alves; Ribeiro, Clovis Augusto [UNESP] (Springer, 2007)
Samples of water based commercial acrylic resin paints were spread in a film form on slides, dried at room temperature and exposed to solar radiation for up to eight months.The characterization and quantification of resins and charges in the white paint emulsion were carried out for the thermal decomposition. Besides this, X-ray diffractometry was used to identify CaCO3 as charge and TiO2 (rutile phase) as pigment.It was observed through thermal techniques similar behavior to the samples even though with varied exposure time.Kinetic studies of the samples allowed to obtain the activation energy (Ea) and Arrhenius parameters (A) to the thermal decomposition of acrylic resin to three different commercial emulsion (called P-1, P-2, P-3) through non-isothermal procedures. The values of E. varied regarding the exposition time (eight months) and solar radiation from 173 to 197 U mol(-1) (P-1 sample), from 175 to 226 W mol(-1) (P-2 sample) and 206 to 197 kJ mol(-1) (P-3 sample).Kinetic Compensation Effect (KCE) observed for samples P-2 and P-3 indicate acrylic resin s present in these may be similar in nature. This aspect could be observed by a small difference in the thermal behavior of the TG curves from P I to P-2 and P-3 sample.The simulated kinetic model to all the samples was the autocatalytic estdk Berggreen.
Keywords: acrylic resin; kinetic parameters; paint emulsions; thermal behavior